Developing the Imagination Skills among Students with Learning Disabilities in English Language - Khasawneh, Mohamad Ahmad Saleem (Journal of Asian Multicultural Research for Social Sciences Study, 2021)
This study explored the effect of active learning on developing imagination skills among students with learning disabilities in English language in Irbid city, Jordan. The study used the experimental approach and was applied to a sample of 60 female and male students, who were chosen purposefully. The sample was divided into two groups, an experimental, which was taught using the active learning method, and a control group, which was taught according to the traditional method. The results revealed the existence of significant differences between the performance of the experimental group and the control group on the post-imagination test in favor of the experimental group. The findings also showed statistically significant differences between the scores of the two study groups on the post-imagination test due to the gender variable, and the difference was in favor of males. In light of the findings of the study, the researcher recommended preparing training programs on active learning and preparing a guide for teachers, which can be used to teach and learn reading, writing, and imagination skills in the basic stage.